2000
DOI: 10.1093/oxfordjournals.molbev.a026420
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine Deamination Plays a Primary Role in the Evolution of Mammalian Isochores

Abstract: DNA melting is rate-limiting for cytosine deamination, from which we infer that the rate of cytosine deamination should decline twofold for each 10% increase in GC content. Analysis of human DNA sequence data confirms that this is the case for 5-methylcytosine. Several lines of evidence further confirm that it is also the case for unmethylated cytosine and that cytosine deamination causes the majority of all C→T and G→A transitions in mammals. Thus, cytosine deamination and DNA base composition each affect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
156
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(168 citation statements)
references
References 67 publications
(92 reference statements)
10
156
1
1
Order By: Relevance
“…Previous studies have shown a positive correlation between GC content and CpG O/E (17,26,27). We also find that the GC content and CpG content are strongly correlated in the A. mellifera genome (Kendall's correlation coefficient, ϭ 0.32; P Ͻ 10 Ϫ15 ).…”
Section: Resultssupporting
confidence: 75%
“…Previous studies have shown a positive correlation between GC content and CpG O/E (17,26,27). We also find that the GC content and CpG content are strongly correlated in the A. mellifera genome (Kendall's correlation coefficient, ϭ 0.32; P Ͻ 10 Ϫ15 ).…”
Section: Resultssupporting
confidence: 75%
“…(These GC ranges divide the data roughly into equal thirds.) Because hypermutable CpG dinucleotides can sometimes skew estimates of the levels of conservation (Fryxell and Zuckerkand 2000), we also recalculated the percent identities after removing all sites that are in a CpG either in human or in mouse. This increased them to 74.4% in low-GC regions, 74.1% in medium-GC regions, and 73.6%, in high-GC regions.…”
Section: Measurement Of Rates Of Neutral Substitutionmentioning
confidence: 99%
“…Cytosine deamination is slowest at pH 8-8.5; the rate increases sharply at higher pH and more gradually at lower pH (when a small positive salt effect is also exhibited). The deamination rates are different for ssDNA and dsDNA; Fryxell and Zuckerkandl (2000) used data from three different sources to obtain the following dsDNA deamination rate: C deamination of double stranded DNA k Cds =2.66 × 10 10 e −32/RT s −1 (R=0.00198 kcal/mol K) (1) Lindahl and Nyberg (Lindahl and Nyberg, 1974) measured cytosine deamination rates in denatured E. coli DNA. At 95 °C and 80 °C, the rates are 2.2 × 10 −7 s −1 and 1.3 × 10 −8 s −1 , respectively.…”
Section: Discussionmentioning
confidence: 99%